2023
DOI: 10.3389/fenvs.2022.1059800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green manure intercropping on soil nutrient content and bacterial community structure in litchi orchards in China

Abstract: Green manure intercropping is an agronomic management practice that effectively increases soil nutrients in understory and reduces weed population. However, the influence of different green manures on soil properties and soil bacterial community in litchi orchards in the tropical regions of China remains largely unknown. Here, we examined the effect of intercropping three leguminous green manure crops in litchi orchards of Hainan Province. No intercropping was used as the control. Different green manures incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Soil AP and NO 3 − -N showed a positive correlation with Bacillaceae, Streptomycetaceae, Paenibacillaceae, and Geodermatophilaceae, as previously observed by Li et al [62], Zhou et al [68], Ribeiro et al [59], and Panhwar et al [69]. This occurs because these plant-beneficial bacteria exhibit a significant potential in N fixation and phosphates solubilization in the soil [65,70]. However, competition with oat signifi-cantly decreased abundance of these beneficial bacteria, resulting in decreasing nutrient acquisition of E. crus-galli and D. sanguinalis.…”
Section: Effect Of Interspecific Competition On Bacterial Community D...supporting
confidence: 81%
See 1 more Smart Citation
“…Soil AP and NO 3 − -N showed a positive correlation with Bacillaceae, Streptomycetaceae, Paenibacillaceae, and Geodermatophilaceae, as previously observed by Li et al [62], Zhou et al [68], Ribeiro et al [59], and Panhwar et al [69]. This occurs because these plant-beneficial bacteria exhibit a significant potential in N fixation and phosphates solubilization in the soil [65,70]. However, competition with oat signifi-cantly decreased abundance of these beneficial bacteria, resulting in decreasing nutrient acquisition of E. crus-galli and D. sanguinalis.…”
Section: Effect Of Interspecific Competition On Bacterial Community D...supporting
confidence: 81%
“…Moreover, the beneficial species (i.e., Bacillaceae, Xanthobacteraceae, Streptomycetaceae, Paenibacillaceae, Planococcaceae, Micromonosporaceae) can favor plant growth and improve nutrient availability by stimulating plants to secrete auxin while simultaneously fixing nitrogen, solubilizing phosphate, and decomposing organic matter [59][60][61][62][63][64]. Apart from their ability to stimulate plant growth, Bacillaceae, Streptomycetaceae, and Geodermatophilaceae can prevent plants from soil-borne disease and abiotic stresses (e.g., drought) through the synthesis of substances akin to lipopeptides that make plants more resistant to external stresses [65,66]. These findings imply that neighboring A. sativa can competitively impair plant growth-promoting bacteria of E. crus-galli and D. sanguinalis, resulting in decreased rhizosphere competence on nutrient uptake, growth, and soil-borne pathogen suppression.…”
Section: Effect Of Interspecific Competition On Bacterial Community D...mentioning
confidence: 99%
“…The community structure and diversity of soil bacteria are important biochemical indicators of soil health, which can be affected by agriculture management ( Li et al, 2022 ; Zhao et al, 2022 ). Intercropping can improve the quantity of orchard soil microorganisms which promote plant growth, enhance plant defenses, and inhibit soil-borne diseases ( Wang et al, 2020 ; Yuan et al, 2023 ). In this study, intercropping marigold improved soil moisture, nutrients and enzyme activities, which may affect rhizosphere organisms, and then influence the structure and diversity of the soil bacterial community ( Cui et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil NH 4 + -N and NO 3 − -N are the principal forms of nitrogen utilized by microorganisms and plants, according to Yuan et al [34]. It was found that modifying the understory vegetation facilitated the accumulation of soil nitrogen pools.…”
Section: Effects Of Understory Vegetation Conversion On Soil C and N ...mentioning
confidence: 99%